2013
DOI: 10.5539/ijbm.v8n15p68
|View full text |Cite
|
Sign up to set email alerts
|

Labor Unrest in the Ready-Made Garment Industry of Bangladesh

Abstract: For the last two decades, Ready-Made Garment (RMG) Industry has been the life-blood of the economy of Bangladesh. This sector accounted for about 80% of the total export earnings of the country. In the recent years, it has been observed that the workers have came down in the street and making insurgence on their demand and tried to destruct public properties. As a result, companies are losing working-hours and production targets. It also hampers export earnings and the image of the country to the international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…In 2014-2015 the industry in Bangladesh was worth USD 25.49 billion that has experienced sharp increases from around USD 10 billion in 2007-2008to USD 17.91 billion in 2010-2011to USD 19.1 billion in 2011(Bangladesh All Party Parliamentary Group, 2013Bangladesh Garment Manufacturers and Exporters Association, 2017;Mottaleb and Sonobe, 2011;Wadud et al, 2014). Currently, the industry accounts for approximately 80-81 percent of export earnings of the country (Ahmed et al, 2013;Akterujjaman and Ahmad, 2016;Bangladesh Garment Manufacturers and Exporters Association, 2017;Curran and Nadvi, 2015;Islam and Ahmed, 2014;Islam and Liang, 2012;Stotz and Kane, 2015;Theuws et al, 2013). The main reason for this explosive growth of the garment industry in Bangladesh is easily available cheap labor (Stotz and Kane, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014-2015 the industry in Bangladesh was worth USD 25.49 billion that has experienced sharp increases from around USD 10 billion in 2007-2008to USD 17.91 billion in 2010-2011to USD 19.1 billion in 2011(Bangladesh All Party Parliamentary Group, 2013Bangladesh Garment Manufacturers and Exporters Association, 2017;Mottaleb and Sonobe, 2011;Wadud et al, 2014). Currently, the industry accounts for approximately 80-81 percent of export earnings of the country (Ahmed et al, 2013;Akterujjaman and Ahmad, 2016;Bangladesh Garment Manufacturers and Exporters Association, 2017;Curran and Nadvi, 2015;Islam and Ahmed, 2014;Islam and Liang, 2012;Stotz and Kane, 2015;Theuws et al, 2013). The main reason for this explosive growth of the garment industry in Bangladesh is easily available cheap labor (Stotz and Kane, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After achieving its independence in 1971, the industry that has been making vital contributions in rebuilding the country and its economy, is now the largest export earner of the country (Adnan et al, 2015;Ahmed et al, 2013;Bangladesh Garment Manufacturers and Exporters Association, 2017;Curran and Nadvi, 2015;Farhana et al, 2015;Hasan et al, 2013;Karmaker and Saha, 2016;Mahmud et al, 2017;Sikdar et al, 2014;Wadud et al, 2014). In 2014-2015 the industry in Bangladesh was worth USD 25.49 billion that has experienced sharp increases from around USD 10 billion in 2007-2008to USD 17.91 billion in 2010-2011to USD 19.1 billion in 2011(Bangladesh All Party Parliamentary Group, 2013Bangladesh Garment Manufacturers and Exporters Association, 2017;Mottaleb and Sonobe, 2011;Wadud et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They are the main power behind the growth but they don't get to decide their fate. Keeping the importance of the ready-made garment industry in the economy of Bangladesh in mind, this study mainly identified the reasons for the continuous labor unrest in this industry of Bangladesh (Ahmed, Raihan, & Islam, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…This sector is considered as the backbone of its economy which is the second largest garment producer and exporter in the world after China (Abdin MJ, 2014). This RMG sector contributes around 82% of Bangladesh's total exports earning and covered around 16% of total GDP (Ahmed, Raihan, & Islam, 2013). Recently Bangladesh garment manufacturer and exporter association (BGMEA) has set a goal to export $50 billion by 2021 and become a largest producer and exporter in the world near future.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…The Main Challenges in this Sector:-Despite RMG industry is the most important and fastest growing sector of Bangladesh's economy it has so many problems and challenges in this sector. The most important problems are political instability, labor unrest lacking of gas, electricity, infrastructure and some bad images (Ahmed et al 2013). In addition, this sector really needs to ensure smooth delivery of products and long-term energy policy.…”
mentioning
confidence: 99%